Optimization of the Automated System in Production - Valentinovna Yudina, Svetlana; Anatolievna Ashirova, Svetlana; Petrovna Mikhailova, Olga; Salavatovich Shamsutdinov, Rustam; Ivanovich Timofeev, Ivan; Zinnatullovna Ryazapov, Liliya (International Journal of Engineering and Technology, 2018)
The article considers practical aspects of automated system optimization in production. Optimal organization of all business processes and monitoring aiming at greater efficiency and profitability of the enterprise is often the main problem of management. For operational decision-making, information about the operation of all company divisions is needed. Obtaining, processing, and presenting such information in the form applicable for further actions, needs a simple convenient tool. A system of enterprise operation automation is designed to perform the role of such a useful auxiliary.The purpose of the present study is to develop and test new modules automating accounting characteristic of the organization and extending beyond the standard solutions, as well as to prove that increasing the collection efficiency of information about the enterprise operation entails a reduction in the complexity of work associated with the accounting and payroll.
Keywords: automated system; software modules; accounting automation; module on surcharges.